An unspeakable hope : brutality, forgiveness, and building a better future for my son - Ford, Leon (Activist) (Atria Books, 2023)
"An unforgettable and stirring memoir in the vein of Free Cyntoia, Just Mercy, and The Sum of Us that both inspires and upends our understanding about the future of policing in the United States. In 2012, nineteen-year-old Leon Ford was shot five times by a Pittsburgh police officer as he was racially profiled during a case of mistaken identity. When he woke up in the hospital, he was faced with two life-changing realities: he was a new father, and he was paralyzed from the waist down. Now, Ford reveals how he faced these new truths and discovered the power of forgiveness and letting go of his hatred. He explains how his harrowing experience inspired his lifelong commitment to social activism. In the wake of countless similar shootings across the country over the years, he has dedicated himself to bridging the gap between the police and the communities they are supposed to serve. With his compassionate voice, Ford not only offers fresh, counterintuitive advice for social change but also demonstrates how together, we can end police brutality and heal as a country. As he once said, "Lead with love. Start compassionate conversations even with individuals and systems that have caused you pain. I know from experience that you can make your pain purposeful.""--